Correlation between the serum eicosapentanoic acid‐to‐arachidonic acid ratio and the severity of cerebral white matter hyperintensities in older adults with memory disorder. (December 2015) - Nagai, Kumiko; Koshiba, Hitomi; Shibata, Shigeki; Matsui, Toshifumi; Kozaki, Koichi
Abstract : Aim: The relationships of n‐3 polyunsaturated fatty acids, such as docosahexaenoic acid and eicosapentaenoic acid (EPA), to stroke and cardiovascular events have been studied extensively. The present study was undertaken to analyze the relationships of the severity of cerebral white matter hyperintensities (WMH) to the blood polyunsaturated fatty acids level and the ratio of serum EPA level to the serum arachidonic acid (AA) level (EPA/AA ratio) among older adults. Methods: A total of 150 patients underwent diagnostic magnetic resonance imaging and blood sampling under the fasting state. In regard to WMH, the periventricular hyperintensities and deep white matter hyperintensities were rated according to the Fazekas classification. The serum docosahexaenoic acid, EPA, AA, dihomo‐γ‐linolenic acid and EPA/AA ratio were compared in relation to the grade of severity of WMH. Furthermore, multiple regression analysis was carried out with age, sex and atherosclerosis risk factors (hypertension, diabetes mellitus, hyperlipidemia, smoking status) as the covariables, serum polyunsaturated fatty acids level as an independent variable and Fazekas grade as the dependent variable. Results: A rise of the periventricular hyperintensities grade was associated with a significant reduction of the mean EPA level ( P  < 0.05) and EPA/AA ratio ( P  < 0.05). The multiple regression analysis identified a significant negative correlation between the periventricular hyperintensities grade and the serum EPA/AA ratio (β = −0.215, P  < 0.05). Conclusion: These results suggest that the serum EPA/AA ratio have an important role in the formation and progression of WMH. Geriatr Gerontol Int 2015; 15 (Suppl. 1): 48–52.